Transitional Justice: What are the Reality and its Concept? - Miftah Idris; Abdul Razak (Rechtsnormen: Journal of Law, 2023)
Background. Transitional justice is an important framework that addresses the ongoing impact of human rights violations and systemic injustice during significant political transitions. Purpose. From the results of this study, it was found that the reality or facts that exist in transitional justice have several existing challenges, besides that there are also several ideal concepts in implementing transitional justice. Method. This research examines the reality and the actual concept of Transitional Justice. In fixing the problem, the researcher uses normative (doctrine) research methods with library data sources as secondary data. Results. includes a comprehensive, victim-centered, and transformative approach. The advice obtained for this research is that it is important to find innovative solutions and involve all stakeholders. Conclusion. includes a comprehensive, victim-centered, and transformative approach. The advice obtained for this research is that it is important to find innovative solutions and involve all stakeholders.